2013
DOI: 10.1063/1.4820015
|View full text |Cite
|
Sign up to set email alerts
|

The mixing of distant sources

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…For typical concentrations, c thr C(x) and the exponential factor in (A20) reduces to exp[−(d/x) β ] : in order to discriminate two different sources by sampling typical concentrations, their separation d must be comparable to the distance x separating the receiver from one source. Our prediction agrees with experimental observations where the cross correlation between the concentration of two scalars emitted by different sources was measured [32]. Conversely, intense events carry more information and allow to tell closer sources apart.…”
Section: Appendix A: Theorysupporting
confidence: 91%
“…For typical concentrations, c thr C(x) and the exponential factor in (A20) reduces to exp[−(d/x) β ] : in order to discriminate two different sources by sampling typical concentrations, their separation d must be comparable to the distance x separating the receiver from one source. Our prediction agrees with experimental observations where the cross correlation between the concentration of two scalars emitted by different sources was measured [32]. Conversely, intense events carry more information and allow to tell closer sources apart.…”
Section: Appendix A: Theorysupporting
confidence: 91%
“…However, in realistic olfactory system, the time-course of receptor activation might provide additional information about which ligands are present. For instance, odors from multiple sources might not fully mix and thus arrive in distinguishable whiffs [50].…”
Section: Resultsmentioning
confidence: 99%
“…Segregating an unknown odorant from a mixture is a blind source separation problem, and solving it requires more information than just the chemical odorant identity (Hendin et al, 1994). The physics of odorant dispersion adds relational information to the chemical odorant identity, as odorants from the same source form plumes with relatively stable odorant concentration proportions (homogeneous plumes), while odorants from different sources form plumes with variable odorant concentration proportions (heterogeneous plumes; Hopfield, 1991; Kree et al, 2013; Celani et al, 2014; Riffell et al, 2014; Soltys and Crimaldi, 2015; Erskine et al, 2019). Indeed, animals can use these relational stimuli to detect whether odorants originate from the same or different sources.…”
Section: Discussionmentioning
confidence: 99%
“…Natural olfactory stimuli are typically mixtures of many different odorants from different sources, which mix together in turbulent plumes (Murlis et al, 1992; Kree et al, 2013; Celani et al, 2014; Riffell et al, 2014; Soltys and Crimaldi, 2015; Erskine et al, 2019). Previous studies suggested that animals perceive odorant mixtures synthetically, that is, they perceive a mixture as a perceptual unit rather than as a list of individual odorants (humans: Jinks and Laing, 1999; squirrel monkeys: Laska and Hudson, 1993; rats: Staubli et al, 1987; spiny lobsters: Lynn et al, 1994, honey bees: Chandra and Smith, 1998; Smith, 1998; Deisig et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation